2‐Hydroxyglutarate concentration in serum from patients with gliomas does not correlate with IDH1/2 mutation status or tumor size - Capper, David; Simon, Matthias; Langhans, Claus-Dieter; Okun, Jürgen G.; Tonn, Jörg-Christian; Weller, Michael; Deimling, Andreas von; Hartmann, Christian (International journal of cancer, 2012)
Abstract IDH1/2 mutations occur at high frequency in diffusely infiltrating gliomas of the WHO grades II and III and were identified as a strong prognostic marker in all WHO grades of gliomas. Mutated IDH1 or IDH2 protein leads to the generation of excessive amounts of the metabolite 2?hydroxyglutarate (2HG) in tumor cells. Here, we evaluated whether 2HG levels in preoperative serum samples from patients with gliomas correlate with the IDH1/2 mutation status and whether there is an association between 2HG levels and glioma size. In contrast to the strong accumulation of 2HG in the serum of patients with IDH1/2 mutated acute myeloid leukaemia, no accumulation was observed in this series of IDH1/2 mutated gliomas. Furthermore, we found no association between glioma size measured by magnetic resonance imaging and 2HG levels. We conclude that 2HG levels in preoperative sera from patients with diffusely infiltrating gliomas of the WHO grades II and III cannot be used as a marker to differentiate between tumors with versus without IDH1/2 mutation. Furthermore, the observation that there is no correlation between 2HG levels and tumor volume may indicate that 2HG cannot be utilized as marker to monitor tumor growth in gliomas.